The application of rainwater harvesting to overcome water crisis in Klang Valley / Muhammad Imran Pandak Othman - Pandak Othman, Muhammad Imran (Faculty of Architecture, Planning and Surveying, 2013)
The purpose of this study is to identify potential of rainwater harvesting to overcome water crisis in Klang Valley. The studies examine the responses of 20% occupants of case studies which are Department of Irrigation and Drainage, National Hydraulic Research Institute of Malaysia and Ministry of Energy, Green Technology and Water. The paper looks at knowledge of people, benefits, system that used for the building, problems and barriers of rainwater harvesting. The data will gather using the questionnaire which will be analysed using the Statistical Package for Social Sciences SPSS version 21. The paper shows that rainwater harvesting has lot of benefits that public not acknowledge the potential. The paper provides original and useful information for developing rainwater harvesting system with effective and efficient.